Two new cultivars of wheat for the Central Brazil region: BR-9 Cerrados and BR-10 Formosa - Silva, Ady Raul da; Andrade, José Maria Vilela de; Leite, Juvenal Caldas (Pesquisa Agropecuaria Brasileira, 2014)
Two wheat cultivars - BR 9 Cerrados and BR 10 Formosa - were bred by the Empresa Brasileira de Pesquisa Agropecuária - EMBRAPA - at the Centro de Pesquisa Agropecuára dos Cerrados - CPAC -, at Planaltina, DF, Brazil, These two new cultivars were recommended by the Technical Council for Evaluation and Recommendation of Wheat Cultivars (Region III.) to farmers of the States of Goiás and Minas Gerais and the Federal District for 1983. BR 9 Cerrados is well adapted for unirrigated cropping, and BR 10 Formosa for irrigated cropping during the dry season. Both cultivars were recommended to farmers due to their better adaptation to the regional environment and their higher yields.